PS02.094: EVALUATION OF ADDITIONAL TREATMENT AFTER NON-CURATIVE ENDOSCOPIC SUBMUCOSAL RESECTION FOR ESOPHAGEAL CANCER. (14th September 2018) - Ohki, Shinji; Hikichi, Takuto; Yamada, Leo; Ujiie, Daisuke; Nirei, Azuma; Tada, Takeshi; Watanabe, Youhei; Hanayama, Hiroyuki; Hayase, Suguru; Gonda, Kenji; Kikuchi, Hitomi; Watanabe, Koh; et al.
Abstract: Background: Recently, endoscopic submucosal dissection (ESD) has been used as a less invasive treatment for superficial esophageal cancer. Additional treatment is often required after non-curative resection to prevent local recurrence and lymph node metastasis. Here, we present the outcomes of various additional treatments for patients with superficial esophageal cancer who underwent ESD. Methods: Between 2006 and 2017, we performed ESD in 179 patients (210 lesions) with superficial esophageal cancer and 44 cases resulted in the non-curative resection diagnosed by the pathological examination. Among them, 29 patients received additional treatment, whereas 15 patients with no additional treatment were followed up. Additional treatment included esophagectomy (8 patients), chemoradiotherapy (15 patients), ablation using argon plasma coagulation (4 patients), and chemotherapy alone (2 patients). We examined the clinicopathological characteristics and prognosis of patients in the additional esophagectomy group (S group) and chemoradiotherapy group (CRT group). Results: Twenty-three patients with pT1a-MM, pT1b, lymphatic invasion, venous invasion, and positive resection margins (both horizontal and vertical) were divided into two treatment groups. Clinicopathological characteristics of patients in the S and CRT groups were not significantly different. Pathological findings after additional esophagectomy showed one residual tumor and one lymph node metastasis. There were no recurrences in the two groups. There was no statistically significant difference in the 5-year overall survival rate between the S group (87.5%) and the CRT group (93.3%). One patient from the S group died due to respiratory pneumonia, and one patient died due to radiation pneumonia. However, five out of the 15 (33.3%) patients who were followed up with no additional treatment developed recurrence. The 5-year overall survival rate was 40.4%, which was not significantly different from that in the additional treatment group. However, the 5-year relapse-free survival rate (30%) was significantly different from that in the additional treatment group ( P  > 0.05). Conclusion: Additional treatment is essential after non-curative endoscopic submucosal resection for esophageal cancer. Additional esophagectomy and chemoradiotherapy were both safe and effective in this cohort. Disclosure: All authors have declared no conflicts of interest.